An Access Authentication Scheme Based on Hierarchical IBS for Proxy Mobile IPV6 Network. Issue 3 (2nd July 2016) - Gao, Tianhan; Tan, Ling; Qiao, Peiyu; Yim, Kangbin
Abstract: Proxy Mobile IPv6 (PMIPv6) enables local network-based mobility management for mobile node without being involved with any mobility-related signalling. However, the lack of access authentication makes PMIPv6 more vulnerable. The literature authentication schemes suffer from low efficiency and suitability. This paper presents a novel efficient authentication scheme for PMIPv6 based on a 2-level identity-based signature scheme. A mutual access authentication protocol is then achieved to eliminate the interactions between the home network and the access network for improving authentication efficiency and reducing communication cost. Moreover, the security and performance analysis demonstrate that the proposed scheme is robust and is able to provide better solution than existing ones.